Cuba-Argentina-Mexico literary stops: from queer-cuir to the unclassifiable - Garduño Dávila , Agni Hazael (Southern perspective / Perspectiva austral, 2024)
Introduction: The article explored the meaning of sexogenic dissidence and its relationship to queer theories, questioning the boundaries of identity and classification. It highlighted how language and labels have attempted to name diverse identities and practices, although without managing to encompass all the existing diversity. The importance of visibility and problematization of the systems that organize and control gender identity and sexuality was also mentioned.Development: It was analyzed how the State and the market have intervened in the classification of identities, either to exercise control or to generate consumption niches within capitalism. Through the examples of Blanco, Sosa and Portela, it was shown how literature has questioned binarisms and power structures that exclude those who do not fit into them. In addition, the need to reimagine spaces of oppression from a Latin American perspective, moving away from an exclusively U.S. interpretation of queer, was highlighted.Conclusion: The article concluded that the visibilization of sex-gender dissidence was not enough if it continued to be absorbed by neoliberal logic. It emphasized the importance of articulating these struggles with other forms of oppression, seeking to deconstruct a dichotomous, modern, colonial and capitalist system. Finally, an approach was proposed that would allow solidarity with other social demands, transcending simple inclusion in the market.